Community-Based Tourism and Stakeholder’s Collaboration: Lessons between Mexico and Spain - SOSA TINOCO, Mariana Monserrat; AULET SERRALLONGA, Silvia; VIDAL CASELLAS, María Dolors (Journal of Environmental Management and Tourism, 2021)
Community-based tourism is widely advocated by academics and professionals as a potential contributor to the conservation and development of a tourism destination. However, other practitioners have questioned whether sustainability goals can be achieved through this form of tourism. Of the various factors reported in the literature that hinder the success of sustainable tourism, the lack of effective collaboration among stakeholders is prominent. This study focuses on stakeholder theories and investigates the contributions of stakeholder collaborations to community-based tourism. For this research, an exploratory design was adopted, in-depth interviews with stakeholders were conducted and the websites of community-based tourism companies in both destinations, Mexico and Spain, were analysed. The results revealed the beginning towards a more local, responsible and sustainable tourism among the stakeholders of community-based tourism. However, community-based tourism in Mexico and Spain has accelerated the replication of this type of tourism, in both tour operators and larger companies, which affects the development of fair trade and the use of natural resources, neglecting communities and benefiting others interests in the tourism industry. Therefore, in remote and resource-poor destinations, the lack of community empowerment and participation jeopardizes the long-term survival of the ecosystems and the local communities themselves.